Serum NOX2 and urinary isoprostanes predict vascular events in patients with atrial fibrillation - Pignatelli, Pasquale; Pastori, Daniele; Carnevale, Roberto; Farcomeni, Alessio; Cangemi, Roberto; Nocella, Cristina; Bartimoccia, Simona; Vicario, Tommasa; Saliola, Mirella; Lip, Gregory Y. H.; Violi, Francesco (Thrombosis and Haemostasis, 2015)
There are limited prospective data evaluating the role of urinary F2-IsoP and NOX2 as predictive markers in atrial fibrillation (AF). The aim of this study was to analyse the role of urinary prostaglandin PGF2alpha (8-iso-PGF2α) and NOX2, markers of systemic oxidative stress, in predicting cardiovascular (CV) events and mortality in anticoagulated non-valvular AF patients. This was a prospective study including 1,002 anticoagulated AF patients, followed for a median time of 25.7 months (interquartile range: 14.8–50.9). All major CV events, CV deaths and all-cause deaths were considered as primary outcomes of the study. CV events included fatal/nonfatal ischaemic stroke, fatal/ nonfatal myocardial infarction (MI), cardiac revascularisation and transient ischaemic attack (TIA). Oxidative stress biomarkers, such as urinary 8-iso-PGF2α and serum sNOX2-dp, a marker of NOX2 activation, were measured. A CV event occurred in 125 patients (12.5 %); 78 CV deaths and 31 non-CV deaths were registered. 8-iso-PGF2α and sNOX2-dp were correlated (Rs=0.765 p> 0.001). A significant increased cumulative incidence of CV events and CV deaths was observed across tertiles for 8-iso-PGF2α and sNOX2-dp. An increased rate of all-cause death was observed across tertiles of urinary 8-iso-PGF2α.In Cox or Fine and Gray models, 8-iso-PGF2α predicted CV events and CV and non-CV deaths. The addition of tertiles of 8-iso-PGF2α to CHA2DS2-VASc score improved ROC curves for each outcome and NRI for CV events (0.24 [0.06–0.53] p=0.0067). The study shows that in AF patients 8-iso-PGF2α and NOX2 levels are predictive of CV events and total mortality. F2-IsoP may complement conventional risk factors in prediction of CV events.Note: The review process for this manuscript was fully handled by Christian Weber, Editor in Chief. Clinical Trial Registration: ClinicalTrials.gov NCT01882114.
Keywords: Arrhythmia; atrial fibrillation; urinary isoprostanes; NOX2; cardiovascular events